Solve for G, F
G=\frac{3\sqrt{5}-23}{22}\approx -0.740536185
F=\sqrt{26}\approx 5.099019514
Share
Copied to clipboard
G=\frac{\left(1-3\sqrt{5}\right)\left(1-3\sqrt{5}\right)}{\left(1+3\sqrt{5}\right)\left(1-3\sqrt{5}\right)}
Consider the first equation. Rationalize the denominator of \frac{1-3\sqrt{5}}{1+3\sqrt{5}} by multiplying numerator and denominator by 1-3\sqrt{5}.
G=\frac{\left(1-3\sqrt{5}\right)\left(1-3\sqrt{5}\right)}{1^{2}-\left(3\sqrt{5}\right)^{2}}
Consider \left(1+3\sqrt{5}\right)\left(1-3\sqrt{5}\right). Multiplication can be transformed into difference of squares using the rule: \left(a-b\right)\left(a+b\right)=a^{2}-b^{2}.
G=\frac{\left(1-3\sqrt{5}\right)^{2}}{1^{2}-\left(3\sqrt{5}\right)^{2}}
Multiply 1-3\sqrt{5} and 1-3\sqrt{5} to get \left(1-3\sqrt{5}\right)^{2}.
G=\frac{1-6\sqrt{5}+9\left(\sqrt{5}\right)^{2}}{1^{2}-\left(3\sqrt{5}\right)^{2}}
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(1-3\sqrt{5}\right)^{2}.
G=\frac{1-6\sqrt{5}+9\times 5}{1^{2}-\left(3\sqrt{5}\right)^{2}}
The square of \sqrt{5} is 5.
G=\frac{1-6\sqrt{5}+45}{1^{2}-\left(3\sqrt{5}\right)^{2}}
Multiply 9 and 5 to get 45.
G=\frac{46-6\sqrt{5}}{1^{2}-\left(3\sqrt{5}\right)^{2}}
Add 1 and 45 to get 46.
G=\frac{46-6\sqrt{5}}{1-\left(3\sqrt{5}\right)^{2}}
Calculate 1 to the power of 2 and get 1.
G=\frac{46-6\sqrt{5}}{1-3^{2}\left(\sqrt{5}\right)^{2}}
Expand \left(3\sqrt{5}\right)^{2}.
G=\frac{46-6\sqrt{5}}{1-9\left(\sqrt{5}\right)^{2}}
Calculate 3 to the power of 2 and get 9.
G=\frac{46-6\sqrt{5}}{1-9\times 5}
The square of \sqrt{5} is 5.
G=\frac{46-6\sqrt{5}}{1-45}
Multiply 9 and 5 to get 45.
G=\frac{46-6\sqrt{5}}{-44}
Subtract 45 from 1 to get -44.
G=-\frac{23}{22}+\frac{3}{22}\sqrt{5}
Divide each term of 46-6\sqrt{5} by -44 to get -\frac{23}{22}+\frac{3}{22}\sqrt{5}.
F=\sqrt{26}
Consider the second equation. Rewrite the division of square roots \frac{\sqrt{52}}{\sqrt{2}} as the square root of the division \sqrt{\frac{52}{2}} and perform the division.
G=-\frac{23}{22}+\frac{3}{22}\sqrt{5} F=\sqrt{26}
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}